KELAS ANTENATAL: STRATEGI PEMBERDAYAAN KADER DAN IBU HAMIL UNTUK PERSIAPAN ORANG TUA DI BONYOH, KINTAMANI - Armini, Ni Wayan; Ayu Harini, I Gusti; Kumala Ratih, Ida Ayu; Astika Dewi, Ni Nyoman (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Stunting remains a national public health challenge, including in Bonyoh Village, Kintamani, Bangli. A preliminary assessment revealed that 50% of pregnant women had limited knowledge of pregnancy care, and 70% had not performed fetal stimulation. This community-based program aimed to strengthen the capacity of health cadres as change agents in supporting pregnant women as the ultimate target through an antenatal class based on an interprofessional education (IPE) approach. The program involved four health professions (midwifery, nutrition, medical laboratory, and dental health) and was implemented through interactive lectures, discussions, demonstrations, prenatal yoga practice, fetal stimulation, and health examinations. A pretest–posttest design without a control group was applied, and the data were analyzed using the Wilcoxon signed-rank test. A total of 20 participants were involved (16 health cadres and 4 pregnant women). The results showed a significant increase in knowledge scores from a mean of 83.64 to 90.02 (p=0.00) and attitude scores from 83.20 to 93.00 (p=0.00). Dental examination identified that 40% of participants had dental caries. These findings indicate that the program effectively improved the capacity of health cadres and enhanced pregnant women’s readiness to maintain a healthy pregnancy and prepare for parenthood. This program is recommended as a community-based intervention model for stunting prevention. Stunting masih menjadi tantangan nasional, termasuk di Desa Bonyoh, Kintamani, Bangli. Hasil asesmen awal menunjukkan bahwa 50% ibu hamil memiliki pengetahuan rendah mengenai perawatan kehamilan dan 70% belum melakukan stimulasi janin. Kegiatan ini bertujuan meningkatkan kapasitas kader kesehatan sebagai agen perubahan dalam mendampingi ibu hamil sebagai target akhir intervensi melalui kelas antenatal berbasis interprofessional education (IPE). Kegiatan melibatkan empat profesi kesehatan (kebidanan, gizi, laboratorium medis, dan kesehatan gigi) melalui metode ceramah interaktif, demonstrasi, diskusi, praktik prenatal yoga, stimulasi janin, serta pemeriksaan kesehatan. Evaluasi dilakukan menggunakan desain pretest–posttest dengan uji Wilcoxon. Sebanyak 20 peserta terlibat (16 kader, 4 ibu hamil). Hasil menunjukkan peningkatan signifikan pengetahuan dari rerata 83,64 menjadi 90,02 (p=0,00) dan sikap dari 83,20 menjadi 93,00 (p=0,00). Pemeriksaan kesehatan menunjukkan 40% peserta mengalami karies gigi. Program ini meningkatkan kapasitas kader dalam memberikan edukasi serta meningkatkan kesiapan ibu hamil dalam menjaga kesehatan kehamilan dan persiapan menjadi orang tua. Program direkomendasikan sebagai model intervensi berbasis desa untuk pencegahan stunting.